Effects on loading calculation of reinforced concrete structural design subjected to fire: review on building codes and standards - Wong, Jing Siong (2019)
This study is to review the relevant building codes and standards for the design of reinforced concrete structural elements under fire condition. Detailed study of the relevant codes and standards for the reinforced concrete design under fire will be carried out. The design requirements will then be identified based on the respective codes requirement or recommendation to identify the differences between the codes in terms of prescriptive and performance design, load combination for fire condition and the design of reinforced concrete structural elements during fire condition. A simple numerical analysis of the reinforced concrete structural element will be carried out to demonstrate the difference in terms of loading calculation adopted for the element design and the reinforced concrete design. The calculation shows that the material strength reduction factor increased when the temperature rises which also affects the flexural strength of the concrete element. However, the reduced permanent and variable actions load factor for the fire condition load combination also reduced the designed moment required, corresponding to the reduction in flexural strength due to the reduced material strength exposed to fire.